2020
DOI: 10.1002/mds.28070
|View full text |Cite
|
Sign up to set email alerts
|

Lower Vitamin B12 Level at Multiple System Atrophy Diagnosis Is Associated With Shorter Survival

Abstract: Background: Multiple system atrophy (MSA) is a neurodegenerative disorder from α-synuclein aggregation. in vitro studies suggest vitamin B12 may interrupt α-synuclein-mediated neurodegeneration. The objective of this study was to determine whether serum vitamin B12 level at MSA diagnosis is associated with survival. Methods: One hundred eighty-two MSA patients evaluated at Mayo Clinic with vitamin B12 testing were studied. We determined the risk of death in relationship to serum vitamin B12 levels at MSA diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…In vitro experiments indicated that vitamin A could potently destabilize preformed alpha-synuclein fibrils, which suggested that vitamin A might be useful in the treatment and prevention of MSA ( Ono and Yamada, 2007 ). McCarter et al (2020) found that low vitamin B12 levels were associated with shorter survival in MSA, implying the potential role as a modifiable survival factor of vitamin B12 for MSA. In addition, a systematic review found supplementation of folate had the potential to reduce the high homocysteine concentrations and other clinical complications in Parkinson’s disease ( Boelens Keun et al, 2021 ).…”
Section: Discussionmentioning
confidence: 90%
“…In vitro experiments indicated that vitamin A could potently destabilize preformed alpha-synuclein fibrils, which suggested that vitamin A might be useful in the treatment and prevention of MSA ( Ono and Yamada, 2007 ). McCarter et al (2020) found that low vitamin B12 levels were associated with shorter survival in MSA, implying the potential role as a modifiable survival factor of vitamin B12 for MSA. In addition, a systematic review found supplementation of folate had the potential to reduce the high homocysteine concentrations and other clinical complications in Parkinson’s disease ( Boelens Keun et al, 2021 ).…”
Section: Discussionmentioning
confidence: 90%
“…37 A natural history study showed that low vitamin B12 levels (< 367 ng/L) were associated with shorter survival (hazard ratio, 1.8; 95% confidence interval, 1.3-2.7), increased frequency of falls within three years of onset, and a lower body mass index, suggesting a potential new target for therapeutic intervention. 14 Another retrospective natural history study revealed that patients with MSA treated with SSRIs showed a better prognosis than untreated patients. 38 Fluoxetine, a second-generation antidepressant categorized as an SSRI, did not affect the primary endpoint.…”
Section: Disease-modifying Therapies and Other Treatmentmentioning
confidence: 99%
“…Other treatments, such as the mammalian target of rapamycin inhibitor sirolimus, which induces autophagy, were ineffective after 48 weeks of treatment [ 37 ]. A natural history study showed that low vitamin B12 levels (< 367 ng/L) were associated with shorter survival (hazard ratio, 1.8; 95% confidence interval, 1.3–2.7), increased frequency of falls within three years of onset, and a lower body mass index, suggesting a potential new target for therapeutic intervention [ 14 ].…”
Section: Disease-modifying Therapies and Other Treatmentmentioning
confidence: 99%
See 2 more Smart Citations